Three-dimensional finite element modelling for prediction corrosion-induced cracking damaged in reinforced concrete beam / Tommy Fong@Ramzi Rimmy, Thevaneyan Krishta David and Zainal Ab. Rahman - Rimmy, Tommy Fong@Ramzi; Krishta David, Thevaneyan; Ab. Rahman, Zainal (2023)
The quality and condition of the reinforced concrete structure is critical, particularly in high-rise buildings where the danger of service life failure is extremely high. Usually, certain structures collapse as a result of cracks and spreading caused by corrosion. Due to this reason, there is a requirement for software program that can promptly measure and evaluate the strength, growth, and longevity of the structure. Researchers use Finite Element Modelling (FEM), a reliable approach to foresee the deterioration and fracturing of structures. The application of finite element modelling in determining the remaining strength of damaged components can provide crucial data, which is particularly relevant for engineers in real-world scenarios. Moreover, it has the ability to replicate the cracking caused by corrosion in reinforced concrete elements. A corrosion-induced cracking model is suggested to be included into a three-dimensional plane-stress finite element model. The cracking model provides an indication of the extent of corrosion-induced damage in the concrete, allowing for the study of strength and behavioural changes. The effect of corrosion-induced cracking in a thick wall cylinder model will be simulated by the finite element model in order to identify and analyse the cracks caused by corrosion in the concrete cover. A corrosion-induced cracking experiment will be conducted with two different cover thicknesses and reinforcement using the Midas FEA commercial software to create a three-dimensional model. There is a slight discrepancy between the numerical analysis modelling and the analytical approach in terms of the crack's initiation and propagation, mostly resulting from variations in modelling assumptions, methods, and parameters. This disagreement arises when comparing the numerical analysis model with the previously published work. Nevertheless, the numerical model may be used to simulate both crack propagation and the critical pressure needed to produce corrosion-induced concrete cover cracking.